PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PERENCANAAN ARAH KARIER SISWA SMA PEMBANGUNAN LABORATORIUM UNIVERSITAS NEGERI PADANG - Nengsih Nengsih (Universitas Islam Negeri Sumatera Utara Medan, 2017)
The phenomenons occur are student not realistic in choosing further education, student not ready to choose further education, and student confused in choosing colleges and majors which they wish to enter. One of the services that used to help career direction planning’s students is a group guidance services. This study aims to determine the effect of group guidance services on the student’s careers direction planning. Research uses quantitative methods. The research type is a Quasi Experiment with the design of the Non-Equivalent Control Group. Subjects of this study amounted to 20 students. The instrument used a scale model of Likert. Research data were analyzed used Wilcoxon Signed Ranks Test of non-parametric statistical, and Kolmogorov -Smirnov 2 Independent Samples with SPSS version 20.00. The results of this research generally that group guidance services influence on the student’s career direction planning. Based on the above findings, it can be concluded that student’s career direction planning can be enhanced with group guidance services.Keywords: Career Direction Planning and Group Guidance Services